Growth Response of Sorghum bicolor (L.) Moench. Cultivars to Trivalent Chromium Stress - Kasmiyati, Sri; Santosa, Santosa; Priyambada, Irfan Dwidja; Dewi, Kumala; Sucahyo, Sucahyo; Sandradewi, Rintawati (Biosaintifika: Journal of Biology & Biology Education, 2016)
One of heavy metal pollutants in the soil that can be absorbed by the sorghum is chromium (Cr). The study was conducted to determine the growth response of Cr3+ stress of sorghum cultivars. Two chemical compounds Cr3+ and 3 level concentrations were exposed to sorghum cultivars. The research was conducted in two separate experiments i.e. during seed germination and early seedling development stages. The parameters measured were radicle/root length, seedling length, fresh weight, dry weight, and stress tolerance index (STI) value. The results showed that Cr3+ either in form of CrCl3 or KCr(SO4)2 significantly reduced the seedling growth of sorghum cultivars. The growth responses of sorghum cultivars toward Cr3+ stress showed differences both on stage of the germination and early seedling. Based on the average of STI value, four sorghum cultivars (Badik, Keris, Keris M3 and Numbu) were classified as very strong tolerant, 4 cultivars (Hegari, Mandau, Sangkur and Gambela) were categorized as moderate tolerant, two cultivars (UPCA and Selayer) were weak tolerant, and 2 cultivars (Kawali and Batari) were sensitive ones, under stress condition of Cr3+.The results of this study are expected to provide the scientific basis of the physiological and tolerance responses of sorghum cultivars toward Cr3+ stress condition.How to CiteKasmiyati, S., Santosa, S., Priyambada, I., Dewi, K., Sucahyo, S., & Sandradewi, R. (2016). Growth Response of Sorghum bicolor (L.) Moench. Cultivars to Trivalent Chromium Stress. Biosaintifika: Journal of Biology & Biology Education, 8(1), 71-84.